Inhibition of progesterone biosynthesis induced by deca-brominated diphenyl ether (BDE-209) in mouse Leydig tumor cell (MLTC-1). (October 2019) - Han, Xiumei; Wang, Yanchen; Chen, Ting; Wilson, Mark J.; Pan, Feng; Wu, Xian; Rui, Can; Chen, Daozhen; Tang, Qiuqin; Wu, Wei
Abstract: Polybrominated Diphenyl Ethers (PBDEs) have been extensively applied as flame retardants in different polymeric materials since the 1970s, which have become a group of long-lasting environmental pollutants. They have been reported from previous studies to accumulate and then disrupt the endocrine system in humans. However, the mechanisms are still little known. In the present study, mouse Leydig tumor cells were utilized to investigate steroidogenic activity influenced by deca-brominated diphenyl ether (BDE-209). Our data showed that BDE-209 did not change intracellular cAMP level in the presence of human Chorionic Gonadotropin (hCG), cholera toxin (CT), and forskolin, which indicated that reduction of progesterone may not be related to the hCG-cAMP signal pathway in MLTC-1 cells. Furthermore, the reduction of progesterone generation was not shifted by 8-Br-cAMP, an analog of cAMP, indicating that BDE-209 may inhibit post-cAMP sites. In addition, mRNA expression levels of P450 side-chain cleavage enzyme (P450scc) and 3β-hydroxysteroid dehydrogenase (3β-HSD) presented a concentration-dependent decrease. In conclusion, this study suggested that BDE-209 may attenuate the progesterone secretion mainly through lowering the expression of these two enzymes. Highlights: BDE-209 may attenuate the progesterone secretion mainly through lowering the expression of P450scc and 3β-HSD. The reduction of progesterone may not be related to the hCG-cAMP signal pathway in MLTC-1 cells. BDE-209 may inhibit post-cAMP sites. Downstream of cAMP may be involved in the reduction of steroidogenic activity instead of cAMP-dependent signal pathway.